2008
DOI: 10.1080/00016340801976012
|View full text |Cite
|
Sign up to set email alerts
|

Serum visfatin levels in late pregnancy and pre‐eclampsia

Abstract: A decrease in visfatin level was demonstrated in pre-eclampsia, suggesting that visfatin and adipokine-associated metabolic abnormalities are involved in the pathogenesis of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
59
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 39 publications
(69 reference statements)
5
59
0
Order By: Relevance
“…It is expressed in the placenta, foetal membranes and myometrium. It was reported that maternal plasma visfatin levels were significantly decreased in women with PE, and furthermore, its levels were correlated with severity of the disease [33]. However, another study reported that serum visfatin levels were higher in women with PE [34].…”
Section: Visfatinmentioning
confidence: 86%
“…It is expressed in the placenta, foetal membranes and myometrium. It was reported that maternal plasma visfatin levels were significantly decreased in women with PE, and furthermore, its levels were correlated with severity of the disease [33]. However, another study reported that serum visfatin levels were higher in women with PE [34].…”
Section: Visfatinmentioning
confidence: 86%
“…Sensitivity analysis was performed by omitting each study in turn and assessing the quality and consistency of the results. Begg's funnel plots and the Egger linear regression test were used to evaluate the publication bias (Hu et al, 2008). All reported P values are two-sided.…”
Section: Discussionmentioning
confidence: 99%
“…Higher visfatin levels were found in IUGR neonates compared with AGA counterparts, probably due to increased visceral adiposity or altered fetal development of adiposity in IUGR subjects [109,110].…”
mentioning
confidence: 95%